Teachers’ Strategies In Implementing The Yanbu’a Method To Improve Students’ Qur’anic Reading Ability In Pesantren - Debi Kurniawan; Widya Andriyani (STAI Al-Mas'udiyah, 2025)
Learning to read the Qur’an constitutes a fundamental foundation in Islamic education, as it is directly related to the understanding of religious teachings, the accuracy of worship practices, and the formation of students’ religious character. This study aims to analyze the role of teachers in the implementation of the Yanbu’a method in improving students’ Qur’anic reading ability at Pondok Pesantren Barokatul Ishlah. This study employed a qualitative approach with a case study design, involving one Qur’anic teacher, eight students, and three pesantren caregivers as informants. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model. The findings indicate that the teacher’s role is both integral and determinant, encompassing functions as planner, recitation model (talaqqi), individual mentor, motivator, and evaluator, all of which are integrated within an adaptive instructional system. The practices of talaqqi and muroja’ah were found to be the primary mechanisms in improving students’ fluency and accuracy in Qur’anic reading, despite challenges such as varying student abilities, limited instructional time, and teacher–student ratio constraintsTh. is study concludes that the effectiveness of the Yanbu’a method does not operate independently, but is highly dependent on the teacher’s pedagogical capacity to manage learning contextually. Therefore, strengthening teacher competence is essential for improving the quality of Qur’anic learning in pesantren settings.